Repetition-Rate-Switchable and Self-Mode-Locked Pulses Generation From a Gain-Switched Thulium-Doped Fiber Laser and Their Amplification Properties - Deqin Ouyang; Junqing Zhao; Zhijian Zheng; Minqiu Liu; Shuangchen Ruan; Jihong Pei (IEEE Photonics Journal, 2017)
We report on repetition-rate-switchable and self-mode-locked pulses generation from a gain-switched thulium-doped fiber laser. Stable pulse trains were gain-switched by a home-made, pulsed Erbium/Ytterbium codoped fiber amplifier. The pulse repetition rate (PRR) of stable output pulse trains can be switched as 1/4, 1/3, and 1/2 times of that of the pump pulse train. Besides, the gain-switched mode-locked pulses were also achieved in the same cavity. By following three-stage thulium-doped fiber amplifiers, the average output power of the stable gain-switched pulses was scaled to 115 W with the PRR of 100 kHz, corresponding to a pulse energy of about 1.15 mJ. The amplification properties of the gain-switched mode-locked pulses were also characterized and discussed.